History of Antitrust Law in Japan - V. N. Shalaevskaya (Теоретическая и прикладная юриспруденция)
This article describes the process of development of Antitrust Law in Japan. The characteristic features of Japanese antitrust regulation in the historical perspective are presented. The effectiveness of the legislation and its problematic issues are analyzed. On the basis of the study, the author propose measures aimed at solving one of the problems of modern antitrust law in Japan, which is contrary to the administrative guidance.